Effects of music training in executive function performance in children: A systematic review - Rodriguez-Gomez, Diego Alejandro; Talero-Gutiérrez, Claudia (Frontiers in Psychology, 2022)
Music training has been hypothesized to enhance the development of executive functions and improve executive performance in children. As a result, music education is considered desirable among curricular education programs worldwide. In this systematic review, we analyze the available evidence of the effects of music training on executive function performance, evaluated using validated neuropsychologic batteries and classic tasks. We observed significant heterogeneity among the music interventions and methods for assessing executive functions. The available literature suggests a beneficial effect of music training in core executive function performance, primarily in inhibitory control, and to a lesser extent, in working memory and cognitive flexibility.